2014
DOI: 10.1590/0001-3765201420120020
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and antioxidant capacity ofTabernaemontana catharinensis A. DC. Fruits and branches

Abstract: The antioxidant capacity of the crude extract and fractions of Tabernaemontana catharinensis fruits and branches, was evaluated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and the content of polyphenols, flavonoids, alkaloids and condensed tannins were determined by the spectrophotometric method. The ethyl acetate fraction of the fruits and the n-butanol fraction of the branches showed IC 50 of 181.82 µg/mL and 78.19 µg/mL, respectively. All fractions were analyzed by high performance liquid chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…In the present study, cinnamic acid derivatives were detected in both the modes of ionization which is in agreement with the previously published data [17]. Chlorogenic acid was earlier reported in Tabernaemontana catharinensis by Piana et al [13] and ferulic acid in Tabernaemontana coronaria by El-Gayed et al [14]. Sinapyl alcohol was documented earlier in cell suspension cultures of Tabernaemontana divaricata by Dagnino et al [18].…”
Section: Benzoic Acid Derivativessupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, cinnamic acid derivatives were detected in both the modes of ionization which is in agreement with the previously published data [17]. Chlorogenic acid was earlier reported in Tabernaemontana catharinensis by Piana et al [13] and ferulic acid in Tabernaemontana coronaria by El-Gayed et al [14]. Sinapyl alcohol was documented earlier in cell suspension cultures of Tabernaemontana divaricata by Dagnino et al [18].…”
Section: Benzoic Acid Derivativessupporting
confidence: 93%
“…However, the positive ionization [M+H] + mode may reveal more structural and fragmentation information about the flavonoid. Plenty of flavonoids synthesized in plants is linked to sugars (glycosides), despite being Previous studies reported the presence of rutin in T. heyneana [8] and Tabernaemontana catharinensis [13]. El-Gayed et al [14] also witnessed the identification of hesperidin in Tabernaemontana coronaria.…”
Section: Identification Of Phenolic Acids Flavonoidsmentioning
confidence: 99%
“…DPPH assay results show that F. benjamina crude extracts presents a high antioxidant capacity, when compared with literature. In fact, a previous paper [29] reported that crude extracts of Tabernaemontana catharinensis fruits and branches, evaluated by the DPPH method and the content of alkaloids, respectively show an IC 50 of 1155.91 mg·ml −1 of fruits crude extract and 202.17 mg·ml −1 of branches crude extract. However, T. catharinensis contained more alkaloids equivalent with respect to F. benjamina.…”
Section: Chemical Composition and Antioxidant Capacitymentioning
confidence: 98%
“…(Apocynaceae), nativa do Rio Grande do Sul (PEREIRA et al, 2008), popularmente conhecida como "cobrina" ou "jasmim-cata-vento" (LORENZI, 2009) demonstrou, em estudos fitoquímicos, ser rica em flavonoides, saponinas, terpenos, alcaloides e esteroides (BÉLO et al, 2009). Seus ramos possuem atividade antioxidante, revelando além da rutina, um glicosídeo de quercetina e ácido clorogênico (PIANA et al, 2014). O chá ou a infusão das folhas e cascas são utilizados na medicina popular brasileira como antídoto para picadas de cobra, para aliviar dor de dente, tratamento de feridas, herpes, tumores e, ainda, como hemostática, hipotensora e cardiotônica (PEREIRA et al, 2005).…”
Section: In Vitro Neoformation Of Aerial Part and Adventitious Rootinunclassified